Mortals and Immortals’ Conflict in Tad Williams's The Heart of What was Lost - Faris, Aveen Arshad (Zanco Journal of Human Sciences, 2024)
Conflict is a literary element that can be defined as a continuous struggle between two opposite forces, it has two main types which are external and internal conflicts. The novel under study is an epic fantasy set in Williams's legendary world of Osten Ard. It depicts the conflict between mortals and fairy people; serving a continuation of prior events between these two races.The aim of the study is to explore the way Williams portrays conflict with its different types to reflect the negative consequences of war. The study is also an attempt to show how these conflicts reflect the agonies and ethical challenges of characters, and that war can only bring decay and shadow. It can be concluded that war results in different types of conflicts and, each of which lead to gloomy ends, to achieve this the text is thoroughly analyzed.